Web-based nutrient management with the software webBESyD–Scientific principles, software architecture and model validation - Joseph Donauer; Marco Luthardt; Christiane Peter; Michael Grunert; Aurelia Ostermaier-Welz; Frank Leßke; Kurt-Jürgen Hülsbergen (Smart Agricultural Technology)
Efficient on-farm nutrient management is a prerequisite for achieving high crop yields, high product quality, high nutrient use efficiency, and low nutrient losses to the environment. So far, software tools are only available for individual, specific management tasks, but there is no comprehensive nutrient management system at farm level. This paper presents the concept, architecture, scientific basis and model validation of the web-based farm nutrient management system webBESyD. This software allows a comprehensive assessment of all relevant nutrient flows within farming systems and is developed specifically for use by farmers and agricultural advisors. webBESyD integrates several scientifically validated modules to calculate fertilizer requirements, nutrient balances, soil organic matter balances, nitrate leaching risks, and to provide decision support. It uses a modular, web-based architecture and interfaces for importing farm, management and geospatial data. All data concerning crop and livestock production is stored centrally in a clearly structured farm model. The modular design allows two different modes of operation: Users can utilize webBESyD directly via a graphical user interface or use specific modules from external systems via a machine-readable application interface. The performance of the modules is evaluated through field experiments, demonstrating good performance. Modeled values align well with measurements, and fertilizer recommendation systems offer economically and ecologically sound guidance. In summary, webBESyD can provide meaningful insights into farm-specific nutrient management, identify optimization potential and provide suggestions for improvement. The technical implementation ensures that webBESyD remains adaptable and compatible with future developments in agricultural technology.